Predictors of Health Behaviors in Turkish Female Nursing Students - Belgüzar Kara, PhD, RN; Bahar İşcan, MS, RN (Elsevier, 2016)
Purpose: This study was conducted to determine the health behaviors of Turkish female baccalaureate nursing students and to examine the impact of sociodemographic and health-related factors and their mothers' health behaviors on the health behaviors of nursing students. Methods: This cross-sectional study included 337 nursing students and 337 mothers. Data were collected using self-administered questionnaires that included a personal information form, the Perception of Health Scale and the Health-Promoting Lifestyle Profile-II (HPLP-II). Descriptive statistics, one-way analysis of variance, Student's t test, Pearson's correlation coefficients and linear regression analysis were used for data analysis. Results: The total HPLP-II mean score of the students was 131.98 ± 17.15 (item M = 2.61, SD = 0.33). Among the subscales of the HPLP-II, the spiritual growth had the highest mean subscale score, followed by the interpersonal relations subscale, while the physical activity had the lowest mean subscale score. Significant predictors of health behaviors of the students were school year (unstandardized β = .09, p = .012), total score for the Perception of Health Scale (unstandardized β = .02, p < .001), and the mothers' total HPLP-II score (unstandardized β = .33, p < .001), after controlling for specific variables. Conclusions: This study demonstrated that the students who were attending the first-year program, those with higher levels of perceptions of health and those whose mothers had better health behaviors were more likely to have better health behaviors. The results of this study emphasize the importance of making culturally appropriate interventions by taking into account the factors contributing to the health behaviors of nursing students.